PERANCANGAN DAN PEMBUATAN SISTEM PENGENDALI ROBOT DENGAN MENGGUNAKAN ISYARAT PUPIL MATA - Supardi, I Wayan; Mamduh, Fahim; Rupiasih, N. Nyoman; Widyatmika, Pt (BULETIN FISIKA, 2012)
It has designed and constructed a robot control system using positions eye pupil cues with motion detection method. The method detects changes in image as a process of movement. The image of the eye pupil was captured by a webcam and subsequently converted into a gray scale. To determine the direction of motion of the prototype robot, has been used the rules of segmentation e.g. the division of area of the image obtained. In every area of an image or segmentation unit will be set to a detector, and if there is movement in that area will be reported in the percentage of movement. Percentage value of the segmentation cells is fed to the parallel port so the prototype robot can move forward, turn right, turn left, and stop.